Characterization of a monolithic immobilized trypsin microreactor with on-line coupling to ESI-MS - Krenková, Jana; Bilková, Zuzana; Foret, Frantisek (Journal of separation science, 2005)
The preparation and characterization of a miniaturized trypsin reactor using on-line coupling with an ESI-TOF mass spectrometer are described. L-1-Tosylamido-2-phenylethyl chloromethyl ketone-trypsin was covalently immobilized on poly(glycidyl methacrylate-co-ethylene dimethacrylate) monolith prepared in a 75 microm ID fused silica capillary resulting in a bioreactor with high local concentration of the proteolytic enzyme. Covalent immobilization of trypsin on this support was performed using the epoxide functional groups in either a one- or a multistep reaction. For on-line protein digestion-MS analysis the bioreactor was coupled with the mass spectrometer using a liquid junction microelectrospray interface. The performance of the reactor was tested using an on-line flow through the system with flow rates of 50-300 nL/min. The resulting protein consumption was in the atto- to low femtomole range. Proteolytic activity was characterized in a wide range of conditions with respect to the flow rate, pH, and temperature. Complete protein digestion was achieved in less than 30 s at 25 degrees C with the sequence coverage of 80% (cytochrome c), which is comparable to 3 h digestion in solution at 37 degrees C. Besides the good performance at laboratory temperature, the immobilized trypsin in the bioreactor also performed well at lower pH compared to the standard in-solution protocols.
Keywords: oxid křemičitý; Capillary Action; indikátory a reagencie; hmotnostní spektrometrie s elektrosprejovou ionizací; Silicon Dioxide; Trypsin; Enzymes, Immobilized; kapilární jevy; trypsin; Tosylphenylalanyl Chloromethyl Ketone; Spectrometry, Mass, Electrospray Ionization; enzymy imobilizované; tosylfenylalanylchlormethylketon; Indicators and Reagents